2014
DOI: 10.1039/c4ob01525h
|View full text |Cite
|
Sign up to set email alerts
|

Stability and bioactivity of thrombin binding aptamers modified withd-/l-isothymidine in the loop regions

Abstract: Thrombin binding aptamer (TBA) is a 15-mer single-strand DNA that was identified by SELEX screening technology. It adopts a chair-type antiparallel G-quadruplex and can specifically interact with thrombin, thus inhibiting blood coagulation. Isonucleoside (isoNA) is a type of nucleoside isomer in which the base is shifted to 2′-positions of the glycosyl group, endowed with the ability to modulate local conformation of nucleotides, and L-isoNA could alter the conformation more due to the inversion of glycosyl co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
1
38
0
1
Order By: Relevance
“…During this work, the authors found that when 3‐phenylpropionic acid was employed as a substrate, only the β‐keto sulfone was obtained with 1,2‐dichloroethane (DCE) as solvent under otherwise identical reaction conditions. Subsequent efforts have been devoted to the system, which was further advanced and applied to the oxysulfonylation of alkynes (Scheme ) …”
Section: Sulfonylationmentioning
confidence: 99%
“…During this work, the authors found that when 3‐phenylpropionic acid was employed as a substrate, only the β‐keto sulfone was obtained with 1,2‐dichloroethane (DCE) as solvent under otherwise identical reaction conditions. Subsequent efforts have been devoted to the system, which was further advanced and applied to the oxysulfonylation of alkynes (Scheme ) …”
Section: Sulfonylationmentioning
confidence: 99%
“…The first thrombin binding aptamer, a 15-mer oligonucleotide, 5′-GGTTGGTGTGGTTGG-3′, was discovered through an in vitro combinatorial selection and polymerase chain reaction process by Bock et al [4]. An increasing number of modified TBAs have since been developed and used for diagnostic and therapeutic applications [59]. Unlike other thrombin-binding biomolecules and proteins, TBAs are smaller mass DNA molecules with high chemical and physiological stabilities, easier to synthesize and have high specificity and affinity for thrombin.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on modifications of TBA with non-natural nucleotides indicate that the improved anticoagulant properties or higher binding affinities of modified variants are often associated with the transformation of the TGT loop. In this way, a few advanced TBA analogs containing 2′-deoxyisoguanosine, 2′-deoxy-2′-fluoroarabinonucleotides, 4-thio-2′-deoxyuridine, 5-hydroxymethyl-2′-deoxyuridine, D-/L-isothymidine and UNA (unlocked nucleic acid) residues in the TGT loop have been described 7 8 9 10 11 12 .…”
mentioning
confidence: 99%